IMPLEMENTASI KEBIJAKAN DALAM PROSES BELAJAR MENGAJAR DI SEKOLAH DASAR MUHAMMADIYAH 2 PEKANBARU - ami, Siti Aminah (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2024)
This study aims to find out and examine the implementation of policies in the teaching and learning process related to the models and methods carried out by teachers to students which are applied in Muhammadiyah 2 Elementary School Pekanbaru. This research is a field research that uses qualitative methods, namely research aimed at analyzing the situation in the field. This study uses data collection techniques by conducting interviews, observation and documentation. Learning methods that have been mastered by the teacher in conveying learning in class have a very important role in the teaching and learning process and are able to create teaching and learning situations effectively and efficiently in accordance with the conditions of students. The results of this study are to examine how the teacher's efforts apply the teaching and learning process standards set in teaching units to produce meaningful learning, with school policies in accustoming students to reading the Koran before starting learning.